Systemic Corticosteroid as an Adjunct for Acute Respiratory Distress Syndrome in Non-Fatal Fresh Water Drowning: An Evidence-based Case Report - Eric Daniel Tenda; Joshua Henrina; Andry Setiadharma; Ceva Wicaksono Pitoyo; Mira Yulianti; Raden Fidiaji Hiltono Santoso; Kuntjoro Harimurti; Czeresna Heriawan Soejono (Acta Medica Indonesiana)
Background: Acute lung injury or acute respiratory distress syndrome (ARDS) is one of the most common complications of non-fatal drowning. Although respiratory societies’ guidelines endorse the role of systemic corticosteroids in ARDS, the evidence for systemic corticosteroids use in ARDS due to non-fatal drowning is limited. Methods: A search was conducted on Pubmed, OVID, and EuropePMC, assessing the clinical question using inclusion and exclusion criteria. The selected studies were critically appraised, and the results were summarized. Results: A total of six retrospective studies were selected and assessed, all studies showed poor validity and a high risk of bias. Out of six studies, only four informed us of steroid administration's effect on outcomes. In two studies, mortality associated with corticosteroid administration seemed to be higher. On the contrary, one study found no mortality in the corticosteroid group, but 100% mortality was observed in the control group. In another study, steroid therapy seemed to not affect hospital length of stay or mechanical ventilation rates. Conclusion: Corticosteroid administration for non–fatal drowning and its impact on clinical outcomes remain equivocal. Routine administration of corticosteroids is not indicated and should be done on a case-by-case basis.